Screening and isolation of compounds with antimicrobial activity produced by multi-resistant bacteria - Espírito Santo, Bruno Miguel Prazeres do, 1989- (2014)
Tese de mestrado. Microbiologia aplicada. Universidade de Lisboa, Faculdade de Ciências, 2014